2017
DOI: 10.1039/c6tc03791g
|View full text |Cite
|
Sign up to set email alerts
|

An erasable photo-patterning material based on a specially designed 4-(1,2,2-triphenylvinyl)aniline salicylaldehyde hydrazone aggregation-induced emission (AIE) molecule

Abstract: An aggregation-induced emission (AIE) molecule with reversible photochromic properties which can be served as a material for photo-patterning with erasable properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 41 publications
0
41
0
1
Order By: Relevance
“…2(a), the crystal structure of A is a tight herringbone arrangement, which is quite common in chain molecule crystals. Compound A crystallizes in the monoclinic system in space group C2/c, and each unit cell has 16 molecules (Wang et al, 2017). A charge on an A molecule can hop to others related by translational symmetry in the same or neighbouring unit cells, as shown in pathways P 1 , P 2 , T 1 , T 2 , T 3 and T 4 (see Fig.…”
Section: Computational Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2(a), the crystal structure of A is a tight herringbone arrangement, which is quite common in chain molecule crystals. Compound A crystallizes in the monoclinic system in space group C2/c, and each unit cell has 16 molecules (Wang et al, 2017). A charge on an A molecule can hop to others related by translational symmetry in the same or neighbouring unit cells, as shown in pathways P 1 , P 2 , T 1 , T 2 , T 3 and T 4 (see Fig.…”
Section: Computational Results and Discussionmentioning
confidence: 99%
“…Recently, a new flexible organic molecule, 4-(1,2,2-triphenylvinyl)aniline salicylaldehyde hydrazone (A), was synthesized by Wang et al (2017), and its spectroscopic properties suggested that the conjugate plane of the phenyl rings could undergo dynamic intramolecular rotation. The high molecular chain flexibility of A is also supported by the weak twisting potential (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The most remarkable outcomeo fa nE SIPT-driven system is the broad,t unable, and dual emission, with al arge Stokes shift, that coversalarge part of the visible-light spectrum. [1][2][3] For theser easons, materials that exhibit the ESIPT phenomenon have been successfully utilized in different optoelectronic applications, for example, in solar concentrators, [5] UV stabilizers, [6] photopatterning, [7] opticalm emory devices, [8] fluorescencei maging, [9] white-light emitters, [10,11] and smarto pticalw riters. Upon excitation, thet wo tautomeric forms give rise to two broad peaks.…”
Section: Introductionmentioning
confidence: 99%
“…Photoluminescent solid‐state materials have attracted significant attention for their wide applications in chemosensors, data recording and storage, dye lasers, organic light emitting diodes (OLEDs) and so on . Development of new multifunctional photoluminescent materials is a research hot spot.…”
Section: Introductionmentioning
confidence: 99%